Effect of NPK fertilizer and biochar residue on paddy growth and yield of second planting - Diana Samira; . Sufardi; . Zaitun; . Chairunas; Anischan Gani; Peter Slavich; Malem McLeod (Syiah Kuala University, 2012)
The objective of experiment was to study effects of NPK fertilizer and Biochar residue on paddy growth and yield of second planting. The research was conducted at Empetrieng village, Aceh Besar district, Aceh Province. The experimental arranged in a randomized complate block design with two factors and four replications. Biochar consisted of two levels, i.e. without biochar residue and with biochar residue 10 ton ha-1. NPK fertilizer consisted of three levels, i.e. without NPK, NPK 60 kg ha-1, and NPK 120 kg ha-1. The result showed that application of NPK significantly affected, plant height 35, 45 and 90 day after planting (DAP), number of tiller 35 and 45 DAP, number of panicle per clump, number of total grain per panicle, percentage of unfilled grain, percentage of filled grain per panicle, 1.000 grain weight, and potential yield per ha. Biochar Residue significantly affected potential yield per ha.